Stock Price Behavior of Acquiring Companies in the Nordics : Short- and Long-Term Value for Shareholders and Value Determinants - Iirola, Amos (My University, 2025)
This thesis examines the stock market performance of acquiring firms in mergers and acquisitions (M&A) within the Nordic region. The study investigates short-term announcement effects, long-term post-acquisition performance, and the deal- and firm-specific characteristics that help explain variation in acquirer outcomes. The objective is to assess whether M&A transactions create value for acquirer shareholders and to identify the factors that influence market reactions. The dataset consists of 138 completed transactions involving publicly listed acquirers from Denmark, Finland, Norway, and Sweden during the period 2000–2020. Iceland is excluded due to its limited number of listed firms and low M&A activity. Short-term performance is measured using the event study methodology based on cumulative abnormal returns (CARs), while long-term performance is evaluated using one-year buy-and-hold abnormal returns (BHARs). Regression models are employed to examine the determinants of announcement and post-acquisition performance, including acquisition premiums, payment methods, and country and industry indicators, as well as the relationship between short- and long-term returns. The results show that Nordic acquirers earn modest but statistically significant positive abnormal returns in short event windows surrounding the announcement date, although the broader [–5, +5] window does not yield a significant effect. Higher acquisition premiums are associated with lower announcement-period returns, while the method of payment does not significantly influence market reactions. In the long term, acquirers do not exhibit systematic underperformance relative to the market, and announcement-period returns do not predict subsequent one-year performance. Some country and industry patterns appear in the regressions, but these effects are mostly not consistent across specifications. The findings suggest that mergers and acquisitions in the Nordic region generate limited short-term value for acquirer shareholders and do not lead to persistent long-term abnormal performance. Market reactions are concentrated around the announcement date, consistent with relatively efficient price adjustment. The results highlight the importance of valuation discipline and deal context in shaping investor responses. Investors appear particularly sensitive to the price paid for targets, as reflected in the negative premium effect, while broader country and sector differences play only a limited role. These insights contribute to the limited empirical evidence on acquirer performance in Nordic capital markets by clarifying the conditions under which M&A announcements generate value for shareholders.

Tässä tutkielmassa tarkastellaan ostajayritysten osakemarkkinasuoriutumista yritysostoissa ja fuusioissa (M&A) Pohjoismaiden alueella. Tutkimus analysoi sekä lyhyen aikavälin markkinareaktioita yritysoston julkistuksen yhteydessä että pitkän aikavälin kehitystä yrityskaupan jälkeen, sekä tekijöitä, jotka vaikuttavat markkinoiden reaktioihin. Tavoitteena on arvioida, luovatko yritysostot arvoa ostajayritysten osakkeenomistajille, ja tunnistaa kauppa- ja yrityskohtaisia tekijöitä, jotka vaikuttavat havaittuihin eroihin tuloksissa. Aineisto koostuu 138 toteutuneesta yritysostosta, joissa ostajana on ollut pörssinoteerattu yhtiö Tanskasta, Suomesta, Norjasta tai Ruotsista vuosina 2000–2020. Islanti on jätetty tarkastelun ulkopuolelle vähäisen yritysostojen määrän ja rajallisen pörssiyhtiömäärän vuoksi. Lyhyen aikavälin suoriutumista mitataan tapahtumatutkimuksen menetelmällä kumulatiivisten epänormaalien tuottojen (CAR) avulla. Pitkän aikavälin suoriutumista arvioidaan yhden vuoden ”osta ja pidä” epänormaalintuoton (BHAR) perusteella. Regressiomalleilla testataan yritysostojen arvonmuodostuksen tekijöitä, kuten maksettua preemiota, maksutapaa, maa- ja toimialavaikutuksia sekä lyhyen ja pitkän aikavälin tuottojen välistä yhteyttä. Tulokset osoittavat, että pohjoismaiset ostajayhtiöt saavat pieniä mutta tilastollisesti merkitseviä positiivisia epänormaaleja tuottoja lyhyiden ilmoitusikkunoiden aikana, vaikka laajempi [–5, +5] tapahtumaikkuna ei tuota merkitseviä tuottoja. Korkeammat yritysostopreemiot ovat yhteydessä heikompiin julkistushetken tuottoihin, kun taas maksutavalla ei ole merkittävää vaikutusta markkinareaktioihin. Pitkällä aikavälillä ostajayhtiöt eivät alisuoriudu systemaattisesti suhteessa markkinoihin, eikä julkistushetken tuotoilla ole ennustearvoa seuraavan vuoden kehitykselle. Regressiot viittaavat joidenkin maa- ja toimialatekijöiden mahdolliseen vaikutukseen, mutta nämä tulokset eivät pääosin ole johdonmukaisia eri mallien välillä. Havainnot viittaavat siihen, että yritysostot Pohjoismaissa tuottavat vain rajallista lyhyen aikavälin arvoa hankkivan yhtiön osakkeenomistajille, eikä niillä ole pysyviä pitkän aikavälin epänormaaleja vaikutuksia. Markkinareaktiot painottuvat ilmoituspäivän ympärille, mikä on yhdenmukaista suhteellisen tehokkaan hinnanmuodostuksen kanssa. Tulokset korostavat arvostuksen ja transaktiokontekstin merkitystä sijoittajien reaktioiden muotoutumisessa. Sijoittajat näyttävät olevan erityisen herkkiä kohdeyhtiöstä maksettavalle hinnalle, mikä näkyy negatiivisena preemioefektinä, kun taas laajemmat maa- ja toimialakohtaiset erot vaikuttavat vain rajallisesti. Nämä havainnot täydentävät rajallista empiiristä tutkimusta pohjoismaisten ostajayhtiöiden suoriutumisesta ja selventävät niitä olosuhteita, joissa yritysostot voivat tuottaa arvoa osakkeenomistajille.
Keywords: mergers and acquisitions, acquirer performance, abnormal returns, event study, CAR, BHAR, Nordic countries, yritysostot ja fuusiot, ostajayrityksen suoriutuminen, epänormaalit tuotot, tapahtumatutkimus, CAR, BHAR, Pohjoismaat